God's Empire Religion and Colonialism in the British World, c.1801-1908 - Carey, Hilary M. (Hilary Mary), 1957- (Cambridge ; New York : Cambridge University Press, 2011)
"In God's Empire, Hilary M. Carey charts Britain's nineteenth-century transformation from Protestant nation to free Christian empire through the history of the colonial missionary movement. This wide-ranging reassessment of the religious character of the second British empire provides a clear account of the promotional strategies of the major churches and church parties which worked to plant settler Christianity in British domains. Based on extensive use of original archival and rare published sources, the author explores major debates such as the relationship between religion and colonization, church-state relations, Irish Catholics in the empire, the impact of the Scottish Disruption on colonial Presbyterianism, competition between Evangelicals and other Anglicans in the colonies, and between British and American strands of Methodism in British North America"--
Part I. God's Empire: 1. Colonialism, colonization and Greater Britain; 2. Protestant nation to Christian Empire, 1801-1908; Part II. Colonial Missions: Introduction: Colonial mission; 3. Anglicans; 4. Catholics; 5. Evangelical Anglicans; 6. Nonconformists; 7. Presbyterians; Part III. Colonial Clergy: 8. Clergy; 9. St Augustine's College, Canterbury; 10. Missionary College of All Hallows, Drumcondra (Dublin); Part IV. Promised Lands: Introduction: Emigrants and colonists; 11. Christian colonization and its critics; 12. Colonies; Conclusion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Great Britain -- Church history -- 19th century; HISTORY / Europe / Great Britain; Electronic books; RELIGION / Christianity / History